From sound to discourse a tagmemic approach to Indian languages - Sharma, Jagdish Chander 1944-.; Central Institute of Indian Languages (Mysore Central Institute of Indian Languages, 1992)
Outcome of a training program organised in 1980.
Keywords: Tagmemics -- Congresses; India -- Languages -- Grammar -- Congresses